An agroecological perspective for improving drought tolerance of wheat cultivars for Sweden - Alamrani, Marwan Mohammed Ismael (SLU/Dept. of Biosystems and Technology (from 130101), 2020)
Drought stress is one of the major abiotic stresses that cause losses in cereal production around the world. Drought stress causes several morphological, physiological, biochemical and molecular transformations in plants. All aspects of plant growth (leaf size, leaf index area and plant height) will be reduced when drought stress is imposed on a plant during all stages of growth. The plant’s physiology under severe drought stress could reduce the transpiration rate and water consumption, which could lead to dried and dead plants, and also affect the quality of grain and cause losses in yield. The drought that happened in the south of Sweden in the 2018 season caused considerable losses in grain yield, primarily winter wheat. The aim of this study was to analyze the effects of drought stress on wheat production in the south of Sweden in the 2018 drought season and then to assess whether new technologies such as phenotyping can provide solutions for the agricultural sector in general and wheat production in particular. The study included two parts: the first part consisted of a five face-to-face interviews. Three interviews were with farmers from different locations in the south of Sweden. The aim of these interviews was to understand the farmers’ perceptions of the drought that happened in 2018 and to explore if they have made plans to handle or prepare for future droughts. The other two interviews were made with plant breeders who work at Lantmännen. The aim of these interviews was to understand how breeders preparing their breeding programs related to climate changing in Sweden and if there are any trials or research relating to drought. The second part of the study consisted of a Biotron experiment to evaluate early vigour and drought stress responses of genotypes. Finally, the analyzed data from the Biotron experiment was compared to drought tolerance scoring obtained from the field trial performed in 2018 for another project. These field score data correlated well with the results of the Biotron experiment. In conclusion, there is a possibility to develop drought-tolerant varieties in wheat which can survive during the drought season. Also, the development in technology sector can provide more accurate tools for phenotyping crops in coming years.